A Novel Induction Machine Model and its Application in the Development of an Advanced Vector Control Scheme - Sokola, M.; Levi, E. (International journal of electrical engineering & education, 2000)
A novel induction motor model, that fully accounts for both the fundamental iron loss and main flux saturation, is derived. The model is then applied to the design of a modified rotor flux oriented control scheme. A rotor flux estimator and a rotor resistance identifier are both developed using the novel model, so that simultaneous compensation of main flux saturation, iron loss and rotor resistance variation is achieved.